Pharmaceutical interventions and factors associated with their acceptance in intensive care units in Brazil - Ana Vitória Martins de Oliveira; Elana Figueiredo Chaves; Amanda Mota Conceição; Liana Moreira Magalhães; Breno Queiroz de Araújo; Cinthya Cavalcante de Andrade; José Martins de Alcântara Neto; Alene Barros de Oliveira (Facultad de Farmacia, Universidad de Granada, 2023)
Abstract Objective: The purpose of this study is to evaluate the pharmaceutical interventions (PI) performed in PRM and the factors associated with their acceptance. Method: This is a descriptive and cross-sectional study that analyzed PIs performed on adult patients from two ICUs in Fortaleza, Brazil, in 2019. PIs were analyzed in the categories quantity of drug and pharmacological strategy, using the classification proposed by Sabater et al. The drugs were also classified by the Anatomical, Therapeutic, and Chemical Classification System and by the High Surveillance Drugs (FAV) classification. Results: 305 patients were included, most of them male (55.1 %), elderly (52.8 %) and treated in the surgical ICU (51.4 %). 1,317 PIs were analyzed and 88.0 % were accepted, being to replace one or more drugs (28.0 %), to add one or more drugs (27.7 %) and to change the dose (24.8 %) the most frequent types. The most prevalent therapeutic class was anti-infectives for systemic use (24.1 %) and AVFs were involved in 21.7 % of the PIs. An association was observed between PIs accepted and admission to the clinical ICU (p<0.0001), AVF (p=0.0013), substitution of one or more drugs (p=0.0062) and the class of blood substitutes and perfusion solutions. (p= 0.0187). Conclusions: A high number of PIs were performed and accepted, which reinforces the importance of the pharmacist in the review of medical prescriptions in the ICU.